EVIDENCE BASED CASE REPORT (EBCR): PENGARUH PIJAT BAYI TERHADAP KUALITAS TIDUR BAYI USIA 3-6 BULAN (Jurnal Kesehatan Siliwangi, 2022)
Background: The prenatal period to toddlers is also known as the golden period, because it is during this time that the brain begins to develop. Stimulation or stimulation can affect how the baby grows and develops in various ways. Baby massage is a form of tactile stimulation for babies. Tactile stimulation is one of the most important things in development. Various studies on the benefits of baby massage show that baby massage can help babies sleep better, strengthen the bond between parents and children, increase the amount of milk production, and can also increase endurance, concentration and body weight. Purpose: This EBCR aims to determine the effect of baby massage on the sleep quality of infants aged 3-6 months. Method: The method in this journal is Evidence Based Case Report. A search for journals was carried out on the Google Scholar portal and the Garuda Portal with the year of publication in 2019. The inclusion criteria in the journal search were full text articles, in English or Indonesian, 2 suitable journals were found and used in writing this EBCR. Results: The results of the EBCR show that the application of baby massage can improve the quality and quantity of baby sleep and strengthen the bond of affection between mother and baby. Conclusion: Baby massage can improve sleep quality in infants aged 3-6 months